The History of Human Rights Law: Generations of Human Rights - Šmigová, Katarína (The Universal Protection of Human Rights, 2026)
Abstract: This chapter provides a study of the historical evolution and conceptual framework of international human rights law. It begins by defining human rights as universal and inalienable entitlements rooted in human dignity, before tracing their philosophical and legal development from ancient times through national milestones like the Cyrus Cylinder, the Magna Carta, the English Bill of Rights, and revolutionary documents from France and the United States. The chapter then explores the transformation of national-level protections into a structured international system following World War II, primarily under the umbrella of the United Nations. The second part of the study aims to classify human rights into four generations: first-generation civil and political rights; second-generation economic, social, and cultural rights; third-generation collective or solidarity rights; and the emerging fourth-generation addressing the challenges of digital technology, artificial intelligence, and biotechnology. Throughout, this chapter emphasises the indivisibility, interdependence, and universality of all human rights. It concludes by underlining the ongoing necessity to adapt human rights law to contemporary technological and societal developments while maintaining its foundational principles of liberty, equality, and human dignity.Keywords: history of human rights law, generations of human rights